2012
DOI: 10.1002/dvdy.23761
|View full text |Cite
|
Sign up to set email alerts
|

Isl1 and Ldb Co‐regulators of transcription are essential early determinants of mouse limb development

Abstract: The developing limb has served as an excellent model for studying pattern formation and signal transduction in mammalians. Many of the crucial genes that regulate growth and patterning of the limb following limb bud formation are now well known. However, details regarding the control of limb initiation and early stages of outgrowth remain to be defined. This report is focused on genetic events that pave the way for the establishment of a hindlimb bud. Fgf10 and Tbx are crucial for early phases of limb bud init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 28 publications
0
37
0
Order By: Relevance
“…We characterized Ldb1 expression in the developing and differentiated retina as it is considered to play fundamental roles and to compensate for Ldb2 loss in various developmental processes (Mukhopadhyay et al, 2003;Narkis et al, 2012). Indeed, Ldb1 seemed to be sufficient to support retinal development, as we did not detect any alterations in OC morphology, differentiation to retinal cell types and lamination in the Ldb1 loxP/loxP ;Ldb2 −/− embryos ( Fig.…”
Section: Ldb1 Is Expressed In Retinal Progenitors and Is Maintained Imentioning
confidence: 90%
See 3 more Smart Citations
“…We characterized Ldb1 expression in the developing and differentiated retina as it is considered to play fundamental roles and to compensate for Ldb2 loss in various developmental processes (Mukhopadhyay et al, 2003;Narkis et al, 2012). Indeed, Ldb1 seemed to be sufficient to support retinal development, as we did not detect any alterations in OC morphology, differentiation to retinal cell types and lamination in the Ldb1 loxP/loxP ;Ldb2 −/− embryos ( Fig.…”
Section: Ldb1 Is Expressed In Retinal Progenitors and Is Maintained Imentioning
confidence: 90%
“…2001). The conditional mutation of Ldb1 was induced on a background of Ldb2 deficiency to preclude any possible compensation for Ldb1 loss by Ldb2 (Tzchori et al, 2009;Narkis et al, 2012). Ldb1 loxP/loxP ;Ldb2 −/− embryos exhibited a normal retinal phenotype, and thus were used as controls (Fig.…”
Section: Ldb1 Is Expressed In Retinal Progenitors and Is Maintained Imentioning
confidence: 99%
See 2 more Smart Citations
“…2C). Interestingly, we observed that LDB1, a LIM-only containing protein often found to be a necessary cofactor of ISL1 in different regulatory contexts (23,24), also binds in vivo to nPE1 and nPE2, but not to the region between them (Fig. 2C).…”
Section: Isl1mentioning
confidence: 92%